Geniposide improves bleomycin-induced pulmonary fibrosis by inhibiting NLRP3 inflammasome activation and modulating metabolism - Yi Wei; Chao Liu; Lujia Li (Journal of Functional Foods, 2023)
Geniposide (Gen) is a natural compound derived from Gardenia jasminoides that has anti-inflammatory, antioxidative stress, antiapoptotic, and antitumour properties. However, its mechanisms of action in idiopathic pulmonary fibrosis (IPF) have not been well studied. Recent studies have found that the progression of IPF is influenced by host metabolism. This study investigated the antifibrotic effects and metabolic modulation of Gen. Gen significantly ameliorated pathological injury in the IPF mouse model. Gen reduced the expression of proinflammatory cytokines and inhibited oxidative stress levels. Gen also inhibited NLRP3 inflammasome activation. Untargeted metabolomics analysis revealed that metabolites were affected in the lung. These metabolites were associated with the regulation of arachidonic acid metabolism, histidine metabolism, and tryptophan metabolism. Gen reduced the inflammatory response and oxidative stress and inhibited NLRP3 inflammasome activation in IPF mice. Mechanistically, Gen-mediated treatment of IPF may be linked to the regulation of host metabolism.